Capsaicinoids, flavonoids, tocopherols, antioxidant capacity and color attributes in 23 native Peruvian chili peppers (Capsicum spp.) grown in three different locations - Meckelmann, Sven W.; Riegel, Dieter W.; Van Zonneveld, Maarten J.; Ríos Lobo, Llermé; Peña Pineda, Karla Mónica; Mueller Seitz, Erika; Petz, Michael (Springer Nature, 2020)
Twenty-three Peruvian chili pepper accessions, belonging to the four domesticated species Capsicum annuum, Capsicum baccatum, Capsicum chinense and Capsicum frutescens, were grown under different meteorological conditions and agricultural practices in three Peruvian locations (Chiclayo, Piura and Pucallpa). Results are reported for powdered oven-dried bulk samples of each accession and each location by important quality attributes (capsaicinoids, flavonoids, tocopherols, antioxidant capacity, total polyphenols, extractable color (ASTA 20.1) and surface color). Multivariate data evaluation by principle component analysis and partial least square discriminant analysis did not show any underlying structure. Moreover, a high influence of the environment on the analyzed traits could be demonstrated by analysis of variance. Significant differences (p ≤ 0.001) between the accessions and all locations were observed for all traits. Besides, significant interaction between accessions and locations indicated that the accessions responded differently to changes of the locations. The calculation of an environmental impact factor allowed differing between chili peppers provided consistent phytochemical levels widely independent of the location or those that provided exceptional high levels for a specific trait at one of the locations.